Spatial analysis of the impact of human activities on the marine environment in Algoa Bay, South Africa - Maphoto, Tidimalo Mary Anne (Rhodes University, Faculty of Science, Department of Geography)
Background: Humans have a long history of using the marine environment in multiple ways and continued use has led to a decline in the ecosystem services provided by marine systems in many places. In addition, human activities have steadily increased with time and advances in technology, further increasing impacts on marine systems. To understand and manage these impacts, we need to assess the spatial distribution and intensity of human activities in the marine environment, and quantify, where possible, their cumulative impacts on marine ecosystems. The spatial consideration of human activities and their associated impacts is important for conservation planning, Integrated Ocean Management and Marine Spatial Planning (MSP) initiatives. The main deliverable of this research study was to develop a cumulative impacts layer of human activities in Algoa Bay, South Africa, to support the Algoa Bay Marine Spatial Planning Project. Objective and Relevance: This research analyses the spatial impacts of human activities on the Algoa Bay marine environment (excluding the seashore). Algoa Bay is located on the south coast of South Africa in the Eastern Cape. The research explores stakeholders' perceptions of their knowledge of the human activities that take place in the bay. This research is informed by an expert-based geographical information systems (GIS) approach and cumulative impact assessment in order to map the spatial impacts of the activities as part of marine spatial planning. "Experts" were defined as stakeholders that contributed valuable knowledge of the human activities and their impacts; this definition of expert included "professional" and "non-professional" contributors to knowledge. The spatial aspect of the research is a significant contribution to the field as it will help inform decision-making in the Algoa Bay Marine Spatial Planning Project. Design and Methods: A mixed-method approach was used to generate data. A snowball sampling approach was used to identify research participants from key informants. Primary data were collected through questionnaire surveys, interviews and a focus group. Secondary data sources consisted of GIS data and reports from scientific organizations. Findings and Conclusion: The research findings indicate that the top three pressures that cause the greatest impact on the Algoa Bay marine environment are fishing, pollution and shipping. The cumulative impact of these activities was highest near harbours in Algoa Bay. The marine ecosystems that were most impacted by pressures were the Agulhas Island and the Agulhas Mixed Shore. The Warm Temperate marine ecosystems had fairly low cumulative impacts. The research findings indicate that there is a complex mix of human activities that impact the marine environment. This research supports the findings of other researchers that reveal that the highest cumulative impact is in areas closer to the coast and harbours owing to high population densities. Value of Study: This study builds onto the existing data by expanding the knowledge base and including more stakeholders to integrate as many human activities as possible and bring a holistic picture of the ocean's uses to inform MSP in Algoa Bay.
Keywords: Marine resources conservation Algoa Bay -- South Africa; Spatial analysis (Statistics); Human ecology; Nature Effect of human beings on; Marine ecology Algoa Bay -- South Africa; Integrated coastal zone management Algoa Bay -- South Africa; Marine spatial planning Algoa Bay -- South Africa